2021
DOI: 10.1016/j.jse.2020.08.036
|View full text |Cite
|
Sign up to set email alerts
|

A new low-profile anatomic locking plate for fixation of comminuted, displaced greater tuberosity fractures of the proximal humerus

Abstract: Background: Although various implants exist for the fixation of isolated greater tuberosity fractures, few implants are specifically designed for such fractures. The purpose of this study was to investigate the clinical and radiologic outcomes of open reduction-internal fixation with a low-profile anatomic locking plate for comminuted greater tuberosity fractures of the proximal humerus. Methods: From November 2012 to February 2018, 24 patients with displaced and comminuted isolated greater tuberosity fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is shown that the elderly are at greater risk of CPHFs in response to slightly larger external stimuli, while young adults often suffer from proximal humeral comminuted fractures under a stronger violent stimulus [ 4 ]. Without timely and effective treatment and intervention, the disease may seriously affect the patient's shoulder joint function, bringing varying degrees of pain and discomfort to patients and even leading to heavy medical pressure on the patient's family and society [ 5 , 6 ]. Therefore, if a clinical treatment strategy with low pain and effective repair of shoulder joint function can be found, it will greatly contribute to the treatment of CPHFs.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the elderly are at greater risk of CPHFs in response to slightly larger external stimuli, while young adults often suffer from proximal humeral comminuted fractures under a stronger violent stimulus [ 4 ]. Without timely and effective treatment and intervention, the disease may seriously affect the patient's shoulder joint function, bringing varying degrees of pain and discomfort to patients and even leading to heavy medical pressure on the patient's family and society [ 5 , 6 ]. Therefore, if a clinical treatment strategy with low pain and effective repair of shoulder joint function can be found, it will greatly contribute to the treatment of CPHFs.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Type III (multi-fragment) fractures should be fixed using a suture bridge or small locking plate to provide stable fixation and early return to function. This surgical technique is simple and efficient [26][27][28]. (iv) Type IV (multi-fragment with medium size RCT) fractures should be fixed using a small locking plate augmented with suture anchors via a mini-open deltoid-split approach [13,16,23,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…Open reduction and internal fixation with locking plates combined or not with suture reinforcement are described as a very useful technique for the treatment of greater tuberosity fractures, especially in osteoporotic bone with big fragments [18,19]. Open plate osteosynthesis provides accurate reduction under direct visualization, rigid fixation of the avulsed fragment, and early mobilization facilitating good functional outcomes, decreasing the possibility of reduction loosening and secondary displacement [20]. The preferred approach for plate fixation is the deltopectoral approach but recent studies have shown promising results with shorter plates that need smaller incisions for placement [14,20].…”
Section: Open Reductionmentioning
confidence: 99%
“…Open plate osteosynthesis provides accurate reduction under direct visualization, rigid fixation of the avulsed fragment, and early mobilization facilitating good functional outcomes, decreasing the possibility of reduction loosening and secondary displacement [20]. The preferred approach for plate fixation is the deltopectoral approach but recent studies have shown promising results with shorter plates that need smaller incisions for placement [14,20]. This lower profile plates, not specific for this greater tuberosity fractures, have been described to avoid or reduce the complication associated with classic plates and maintaining the rates of union and functional recovery [20].…”
Section: Open Reductionmentioning
confidence: 99%
See 1 more Smart Citation